The Embeddedness of Urban Climate Politics in Multilevel Governance: A Case Study of South Africa's Major Cities. (March 2019) - Hickmann, Thomas; Stehle, Fee
Numerous scholars have lately highlighted the importance of cities in the global response to climate change. However, we still have little systematic knowledge on the evolution of urban climate politics in the Global South. In particular, we lack empirical studies that examine how local climate actions arise in political-administrative systems of developing and emerging economies. Therefore, this article adopts a multilevel governance perspective to explore the climate mitigation responses of three major cities in South Africa by looking at their vertical and horizontal integration in the wider governance framework. In the absence of a coherent national climate policy, Johannesburg, Cape Town, and Durban have developed distinct climate actions within their jurisdictions. In their effort to address climate change, transnational city networks have provided considerable technical support to these cities. Yet, substantial domestic political-economic obstacles hinder the three cities to develop a more ambitious stance on climate change.